Acute poisoning by organophosphorus pesticides: an integrative review (Research, Society and Development, 2022)
Organophosphate pesticides can cause intoxication in exposed individuals. The objective of this work was to carry out an integrative review on acute human intoxication by organophosphate pesticides. The search for scientific articles was carried out in the CAPES Journals Portal and in the Scopus database using the combination of the descriptors “organophosphates”, “cholinesterase” and “acute intoxication” interrelated by the Boolean localizer “AND”. Works in English and Portuguese, published between 2016 and 2021 were considered. 146 articles were identified and after reading the title and abstract, 26 potentially eligible articles were selected, which were read in full, observing if, in fact, they met the criteria settled down. After reading, 19 articles were selected to compose the review. Studies report the importance of measuring cholinesterases in the assessment of acute poisoning by organophosphate pesticides, however, most perform the dosage without the basal value of these enzymes. Although the Ellman method is the most common form of quantification, there are many methodological variations. Thus, it is essential to study new markers for acute intoxication and to optimize existing methodologies. The symptoms that affect individuals are nonspecific and may be related to the specific active ingredient of each organophosphate. Factors such as lifestyle, presence of metabolic alterations, low education, advanced age, low use of PPE and inappropriate use of pesticides are also associated with cases of intoxication. The training and awareness of individuals who handle organophosphates, in addition to actions by the government, are essential to strengthen regulations on the use of these substances, in order to avoid health problems in the population.